Morphological and complete genome analysis of a novel Clostridium perfringens phage CpP_VarHS, isolated from wastewater - Saghrouchni, Hamza; Tasdurmazli, Semra; Kilic, Ibrahim Halil; Var, Isil (FRONTIERS MEDIA SA, 2026)
Introduction Various systemic and enteric diseases have been attributed to C. perfringens, including healthcare-associated infections and intoxications. Humans and animals are thus exposed to serious health risks from these bacteria. Infections caused by these antibiotic-resistant bacteria are becoming an increasing concern. Bacteriophages (phages), which possess specific lytic activity, offer a viable alternative for the treatment of Clostridium perfringens.Methods In this study, a novel lytic C. perfringens phage designed as CpP_VarHS was isolated from wastewater and targeted the host C. perfringens type A ATCC 13124. The phage was then characterized using Transmission Electron Microscope (TEM), molecular sequencing, and bioinformatics tools.Results Transmission electron microscopy (TEM) analysis revealed that CpP_VarHS possesses a short, non-contractile tail (31.55 +/- 2.5 nm in length) and a regular icosahedral head (44.23 +/- 2.1 nm in diameter), characteristic of the podovirus morphotype. Whole-genome analysis showed that the CpP_VarHS genome is 17,814 bp long, linear double-stranded DNA with a GC content of 28.30%. Among the 21 identified open reading frames, 12 were functional genes (GenBank accession number PP973485). Whole-genome sequence comparison showed 94.37% and 94.31% nucleotide identity with Clostridium phage vB_CpeP_HN02 and Clostridium phage CPS1. No tRNA, bacterial virulence gene, lysogenic gene, or antibiotic resistance gene was identified in the genome of CpP_VarHS. Phylogenetic analysis indicated that phage CpP_VarHS represents a novel species within the genus Gregsiragusavirus of the family Guelinviridae.Conclusion To the best of our knowledge, this is the first report of the isolation of a C. perfringens phage in T & uuml;rkiye. In conclusion, these findings suggested that phage CpP_VarHS has promising potential for preventing and controlling C. perfringens.
Keywords: antibacterial activity; Clostridium perfringens; lytic bacteriophage; molecular sequencing; transmission electron microscope; phage therapy; UNITED-STATES; SEQUENCES; VIRULENT; ILLNESS; Pharmacology & Pharmacy